Engaging older patients with cancer and their caregivers as partners in cancer research. Issue 23 (16th August 2019) - Gilmore, Nikesha J.; Canin, Beverly; Whitehead, Mary; Sedenquist, Margaret; Griggs, Lorraine; Finch, Lynn; Grossman, Valerie; Targia, Valerie; Wells, Megan; Kamen, Charles; Flannery, Marie; Magnuson, Allison; et al.
Abstract : Active patient partner engagement with Stakeholders for Care in Oncology and Research for our Elders board (a diverse group of older patients with cancer, caregivers of older patients with cancer, survivors, and patient advocates) to conduct what, to the authors' knowledge, is the largest randomized geriatric assessment clinical trial published to date has been shown to be feasible and to result in tangible and invaluable benefits for both the research team and patient partners alike. Actively engaging patient partners should be an essential component of the development, conduct, and completion of all clinical research.